2022
DOI: 10.1093/mtomcs/mfac001
|View full text |Cite
|
Sign up to set email alerts
|

Zinc sequestration by human calprotectin facilitates manganese binding to the bacterial solute-binding proteins PsaA and MntC

Abstract: Zinc is an essential transition metal nutrient for bacterial survival and growth but may become toxic when present at elevated levels. The Gram-positive bacterial pathogen Streptococcus pneumoniae is sensitive to zinc poisoning, which results in growth inhibition and lower resistance to oxidative stress. S. pneumoniae has a relatively high manganese requirement and zinc toxicity in this pathogen has been attributed to the coordination of Zn(II) at the Mn(II) site of the solute-binding protein (SBP) PsaA, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Zinc-binding proteins: Several studies have investigated the binding properties of these proteins and their impact on bacterial survival. In 2022, Rosen et al [69] demonstrated that the solute-binding proteins (SBPs) called PsaA and MntC in Streptococcus pneumoniae and Staphylococcus aureus, respectively, bind Zn reversibly and exhibit a preference for Zn ions over other metals. Researchers have uncovered several mechanisms by which bacteria resist zinc toxicity.…”
Section: Anthropogenicmentioning
confidence: 99%
“…Zinc-binding proteins: Several studies have investigated the binding properties of these proteins and their impact on bacterial survival. In 2022, Rosen et al [69] demonstrated that the solute-binding proteins (SBPs) called PsaA and MntC in Streptococcus pneumoniae and Staphylococcus aureus, respectively, bind Zn reversibly and exhibit a preference for Zn ions over other metals. Researchers have uncovered several mechanisms by which bacteria resist zinc toxicity.…”
Section: Anthropogenicmentioning
confidence: 99%
“…196 Interestingly, by reducing sensitivity to zinc poisoning, CP may inadvertently benefit bacterial pathogens instead of the host, eg, via sequestration of Zn from high-affinity manganese transporter PsaA of highly sensitive to zinc poisoning pathogen S. pneumoniae. 197 Finally, production of high-affinity Zn transporter ZnuABC transporter allows Salmonella enterica to overcome CP-mediated Zn sequestration, and, in turn, to outcompete intestinal commensals and survive in the inflamed intestine. 76…”
Section: Dovepressmentioning
confidence: 99%
“…The proposed mechanism involves the displacement of Mn 2+ by Zn 2+ in the PsaA protein, thereby hindering the uptake of Mn 2+ and resulting in a deficiency of this cation within the cytoplasm ( Jacobsen et al, 2011 ; Counago et al, 2014 ). Nevertheless, throughout the course of pneumococcal infection, both CP ( Rosen et al, 2022 ) and calgranulin ( Rosen and Nolan, 2022 ) have the ability to sequester Zn 2+ from PsaA, facilitating the binding of Mn 2+ to this protein and subsequent uptake of Mn 2+ . Interestingly, these proteins, which are employed by host cells as antimicrobial agents, paradoxically promote bacterial pathogenesis in this particular context.…”
Section: Manganese Transport Systemsmentioning
confidence: 99%